Life-threatening unilateral hearing impairments. Review of the literature on the association between inner ear malformations and meningitis. Issue 12 (December 2015) - Muzzi, E.; Battelino, S.; Gregori, M.; Pellegrin, A.; Orzan, E.
Abstract: Background: Bacterial meningitis is a life threatening disease that can be triggered by a CSF leak through an inner ear malformation. Early identification of the specific type of cochleovestibular dysplasia and the associated risk of meningitis is of vital importance. Objectives: The objective of this review is to collect and discuss available data on the association between inner ear malformations and meningitis in children. Methods: Electronic databases were crosschecked for obtaining relevant papers published in the last 20 years, and further cases were identified by hand searching through the references. Demographic data were extracted from full texts, together with information on the severity of hearing impairment, the type of inner ear anomaly, the site of cerebrospinal fluid leak, the number of recurrent meningitis episodes. Results: Sixty-seven cases of meningitis related to inner ear malformation have been identified among 45 papers. Mean age at presentation is 3.60 ± 3.00 (range 0.1–14) years. Average diagnostic delay from the first episode of meningitis is 3.44 ± 3.41 (range 0.00–10.00) years. The number of meningitis episodes that occurred before the correct diagnosis and definitive surgical treatment is 3.27 ± 1.81 (range 1.00–10.00). Unilateral hearing impairment affects 70% of patients. Six patients had normal hearing at presentation. Two children are dead from inner-ear-malformation-related meningitis among reviewed reports. Conclusion: A high number of paediatric patients carrying inner ear malformations, especially when associated with unilateral hearing impairment, could be at risk to develop recurrent bacterial meningitis. Universal newborn hearing screening programs should prompt a diagnostic work-up even in the case of unilateral hearing impairment, in order to prevent inner ear malformation-related meningitis.